The London bookshop affair : a novel of the Cold War - Fein, Louise (William Morrow, an imprint of HarperCollins Publishers, 2024)
"London, 1962: The world is teetering on the brink of nuclear war but life must go on. Celia Duchesne longs for a career, but with no means or qualifications, passes her time working at a dusty bookshop. The day a handsome American enters the shop, she thinks she might have found her way out of the monotony. Just as the excitement of a budding relationship engulfs her, a devastating secret draws her into the murky world of espionage. France, 1942: Nineteen-year-old Anya Moreau was dropped behind enemy lines to aid the resistance, sending messages back home to London via wireless transmitter. When she was cruelly betrayed, evidence of her legacy and the truth of her actions were buried by wartime injustices. As Celia learns more about Anya, and her unexpected connection to the undercover agent, she becomes increasingly aware of furious efforts, both past and present, to protect state secrets. With her newly formed romance taking a surprising turn and the world on the verge of nuclear annihilation, Celia must risk everything she holds dear, in the name of justice."--